Single-Patient Expanded Access Requests: IRB Professionals' Experiences and Perspectives. Issue 2 (3rd April 2019) - Chapman, Carolyn Riley; Shearston, Jenni A.; Folkers, Kelly McBride; Redman, Barbara K.; Caplan, Arthur; Bateman-House, Alison
Abstract: Background: U.S. physicians may treat a patient with an investigational drug outside of a clinical trial by using the expanded access (EA) pathway or the recently created federal right to try (RTT) pathway. The EA pathway requires physicians to get prior permission from the U.S. Food and Drug Administration (FDA) and, except in emergency cases, institutional review board (IRB) approval. The perspectives of IRB professionals on the review of single-patient EA requests have not been empirically studied.Methods: We used a cross-sectional online survey to ascertain IRB professionals' perspectives on IRB experiences with and preparedness for review of single-patient EA requests, as well as their attitudes about the importance of IRB review of such requests. Email invitations were sent to 234 IRB professionals connected to the SMART IRB platform. Approximately half of the survey questions used a Likert scale to assess respondents' agreement with specific statements.Results: Eighty-three respondents completed the survey (36.4% response rate, with 228 deliverable e-mail invitations). Of the respondents, 73.5% were affiliated with an academic medical institution; 78.3% of respondents agreed that it is important for a designated member of an IRB to review single-patient EA requests before investigational drugs are used by patients. The majority indicated that local review of the EA request was important and that a single designated reviewer was sufficient (rather than full board). Further, 86.6% felt that their IRBs were prepared to review these requests, and 9.2% indicated that not all the single-patient EA requests reviewed by their IRBs in 2017 were approved.Conclusions: A large majority of IRB professionals affiliated with the SMART IRB platform who responded to this survey felt IRB review of single-patient EA requests is important and that their IRBs were prepared to handle such requests.